Optimal exercise dose and type for improving sleep quality: a systematic review and network meta-analysis of RCTs - Li, Li; Wang, Chunxiao; Wang, Dandan; Li, Hua; Zhang, Shuai; He, Yuanchun; Wang, Ping (Frontiers in Psychology, 2024)
Background A substantial amount of research has explored the intricate relationship between exercise and sleep quality, consistently confirming that exercise can effectively enhance sleep quality. Nevertheless, previous studies have yet to conclusively determine which specific exercise program is most efficacious in improving sleep quality. To address this gap, the present study systematically evaluated the differential effects of various types of exercise, as well as exercise dosages (including duration, intervention period, frequency, and intensity), on sleep outcomes using a network meta-analysis approach. This endeavor aims to provide evidence-based support for the development of scientifically effective exercise programs tailored to improve sleep quality. Methods Through the Web of Science, PubMed, Cochrane Library, Embase, and Scopus databases, we conducted a search for randomized controlled trials investigating the effects of exercise interventions on sleep, with a search cutoff date of April 30, 2024. We rigorously selected the literature according to the PICOS principle, and two independent researchers extracted the data. We would like to change this passage to: Bias risk assessment was conducted using the RevMan 5.4 software, and traditional meta-analysis and network meta-analysis were performed using Stata 17.0 software to generate forest plots, network evidence plots, and funnel plots. Furthermore, we adopted the surface under the cumulative ranking curve (SUCRA) to evaluate and rank the intervention effects of different exercise types and dosages on sleep quality. To verify the robustness of our study results, we performed a sensitivity analysis using the leave-one-out method. Results The study strictly adhered to the PRISMA guidelines and included 58 RCT papers with a total of 5,008 participants. The network meta-analysis revealed significant variations in the impact of exercise frequency on sleep outcomes when compared to the control group. Interventions of 1–2 times per week [SMD = −0.85, 95% CI (−1.43, −0.26)], 3 times per week [SMD = −0.45, 95% CI (−0.80, −0.11)], and 4 times per week [SMD = −1.09, 95% CI (−1.92, −0.26)] demonstrated the most notable effects. Interventions lasting ≤30 min and 60–65 min were significantly more effective than the control group, with ≤30 min proving significantly more effective than 40–55 min [SMD = 0.75, 95% CI (0.01, 1.49)]. Interventions lasting 9–10 weeks [SMD = −1.40, 95% CI (−2.37, −0.44)], 12–16 weeks [SMD = −0.55, 95% CI (−0.90, −0.20)], and ≥ 24 weeks [SMD = −0.71, 95% CI (−1.31, −0.10)] were all significantly more effective than the control group. Additionally, the 9–10 weeks intervention period was found to be significantly more effective than the 6–8 weeks period [SMD = −1.21, 95% CI (−2.37, −0.04)]. Furthermore, interventions of moderate intensity [SMD = −1.06, 95% CI (−1.52, −0.61)] and high intensity [SMD = −1.48, 95% CI (−2.55, −0.40)] exercise interventions yielded significantly greater benefits compared to the control group. Specifically, high intensity interventions [SMD = −1.97, 95% CI (−3.37, −0.56)] and moderate intensity [SMD = −1.55, 95% CI (−2.57, −0.54)] exercise interventions were found to be significantly more effective than moderate-high intensity interventions. In terms of exercise types, aerobic exercise [SMD = −0.56, 95% CI (−0.86, −0.27)], traditional Chinese exercises [SMD = −0.57, 95% CI (−0.97, −0.18)], and combined exercise [SMD = −0.99, 95% CI (−1.66, −0.32)] interventions all produced significant improvements compared to the control group. The study determined that the most effective combination of exercise prescription elements for enhancing sleep quality includes a frequency of 4 times per week (SUCRA = 84.7), a duration of ≤30 min (SUCRA = 92.2), a period of 9–10 weeks (SUCRA = 89.9), and high-intensity (SUCRA = 92.9) combined exercise (SUCRA = 82.7). Conclusion The current evidence indicates that combined exercise with a frequency of 4 times per week, a duration of ≤30 min, a period of 9–10 weeks, and high intensity is most effective for improving sleep quality. Nevertheless, due to the limited number of studies included, further research is needed to enhance the reliability of the findings. Systematic review registration https://www.crd.york.ac.uk/prospero/, identifier: CRD42024555428.